Accelerated epithelialization and improved wound healing metrics in porcine full‐thickness wounds transplanted with full‐thickness skin micrografts1. Issue 5 (11th October 2017) - Rettinger, Christina L.; Fletcher, John L.; Carlsson, Anders H.; Chan, Rodney K.
Abstract: Split‐thickness skin grafting (STSG) is the current gold standard for treatment of extensive burn and traumatic skin injuries. However, STSG is limited by donor‐site morbidity and availability, and often leads to scarring and wound contracture. Furthermore, these thin grafts lack dermal elements such as nerves and adnexa which are important in recapitulating normal skin function. Methods of fractional skin replacement either as minced STSGs or microscopic skin tissue columns have been proposed, though these techniques have not been fully characterized and lack evidence of regenerated adnexal structures. Here, we describe an alternative method of fractional skin replacement using full‐thickness skin micrografts containing deep dermal components and intact adnexa. Full‐thickness wounds measuring 3 cm in diameter and 2 cm apart were created on adult female Yorkshire swine. Full‐thickness skin tissue columns (FTSTCs) 1.5 mm in diameter with intact adnexa and subcutaneous tissue were obtained using a suction‐assisted device. Explant culture was initiated to demonstrate the capacity of FTSTCs to act as reservoirs of viable and proliferative epidermal and dermal cells. FTSTCs were applied directly to excisional wounds at three different expansion ratios (1:16, 1:40, 1:100) in fibrin sealant. Biopsies were collected at defined time points postwounding and processed for histology and immunohistochemistry. Wounds grafted with FTSTCs showed enhanced reepithelialization and epidermal differentiation over untreated control wounds in a dosage dependent manner. Adnexal structures such as hair follicles and sweat glands were only evident in FTSTC‐treated wounds. Furthermore, whereas ungrafted wounds were marked by extensive infiltration of α‐Smooth Muscle Actin + (α‐SMA + ) myofibroblasts at POD 60, α‐SMA expression was sparse and largely limited to perivascular cells in FTSTC‐treated wounds. The number of Ki67 + cells was also greatly reduced in FTSTC‐treated wounds. Transplantation of FTSTCs containing intact adnexa improved wound healing parameters in porcine full‐thickness wounds and may have implications for the treatment of large, traumatic wounds.